PENERAPAN MODEL PERTEMUAN KELAS DALAM MENINGKATKAN SIKAP SOSIAL DAN TANGGUNG JAWAB SISWA SEKOLAH DASAR - Asih Asih (Jurnal Komunikasi, 2026)
This study aims to examine the application of the class meeting model in improving elementary school students' social attitudes and sense of responsibility through a qualitative literature study approach. The class meeting model, developed by William Glasser, emphasizes group discussion, active participation, and collaborative problem-solving. Through a review of relevant literature, this study finds that the class meeting model consistently has a positive effect on students' social attitudes, including cooperation, communication, and empathy. Furthermore, this model has been shown to foster students' sense of responsibility toward themselves and their environment. Effective implementation requires thorough planning by the teacher, a conducive classroom environment, and integrated curriculum support. This study concludes that the class meeting model is worth considering as an alternative character education strategy in elementary schools.